Manajemen Kebidanan Berkesinambungan : Studi Kasus Pada Ibu Dengan Asuhan Komprehensif - Sri Dewi Haryati; Desi Ernita Amru (Jurnal Anestesi, 2023)
Indicators to measure the quality of health services in an area can be seen from the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). One of the ways that can be done to reduce maternal mortality (MMR) and infant mortality (IMR) is by implementing continuous care. The purpose of this continuous midwifery care is to be able to provide comprehensive midwifery care to Mrs. "S" from pregnancy to family planning in accordance with midwifery care standards. Case study research method. The results of the implementation of midwifery care on an ongoing basis (Continuity of Care) on Mrs. "S" G1P0A0 age 24 years starting from the gestational age of 30 weeks 3 days to the age of 38 weeks. At the first pregnancy visit there was a problem in the mother, namely pregnancy with breech location. At the second visit the baby's position was in a normal position. The delivery process ended by cesarean section because the baby had an Early Rupture of Membranes. The baby was born at Budi Kemuliaan Hospital with a weight of 3000 gr Body Length : 48 cm Head Circumference: 33 cm, Chest Circumference: 32 cm. In the postpartum period, physiological complaints were found such as pain in the suture wound but not accompanied by signs of suture wound infection. Mrs. "S" chose to use 3-month injectable birth control. The conclusion of this assessment is that midwives are expected to be able to provide comprehensive care from pregnancy to family planning services and apply care in accordance with midwifery service standards.